Evaluation of an international faculty development program for developing countries in Asia: the Seoul Intensive Course for Medical Educators. Issue 1 (December 2015) - Kim, Do-Hwan; Yoon, Hyun; Sung, Minsun; Yoo, Dong-Mi; Hwang, Jinyoung; Kim, Eun; Lee, Seunghee; Shin, Jwa-Seop
Abstract Background The issue of collaboration in medical education is becoming prominent. Some faculty development programs have suggested an approach for promoting collaboration on a global level. However, non-English-speaking developing countries in Asia, especially in Southeast Asia, do not take advantage of them due to their unique context, such as language and culture. To address these issues, Seoul National University College of Medicine initiated a 6-week international faculty development program called the "Seoul Intensive Course for Medical Educators" for 16 fellows from five Asian countries (Cambodia, Laos, Mongolia, Myanmar, and Vietnam). The aim of this study is to report the evaluation results of the outcome of the program and discuss better ways of collaborating with developing countries. Methods Three levels of collaboration—intraorganizational, intranational, and international—were central initiatives of the program. Prior to setting up the program details, we first established four design principles, following which the contents, materials, and facilitators were determined to maintain consistency with the design principles. The evaluation of the program was done with Kirkpatrick's four-level model. Most of the evaluation data for level 1 were collected by two questionnaires, the post-module survey and the post-program survey. Portfolios and progress reports were mainly used to collect outcome data for levels 2 and 3, respectively. Results The reaction was generally positive throughout the program and there was a significant correlation between satisfaction and relevance to one's job or needs. Despite the fellows' propensity for overestimating themselves, both the evaluators and fellows reported that there was significant improvement in learning. Opinions on the impact or urgency of the topics were slightly different from country to country; however, the answers regarding feasibility were fairly similar. Moreover, we could observe from the post-program progress reports that the transfer of learning was actively in progress, mainly for topics that were highly feasible. Conclusions These results show that the program was successful in terms of its effectiveness. Consistent and timely support is essential for the sustainable development of the medical education systems in these countries. Further understanding of the underlying factors on transfer (level 3) could improve the effectiveness of faculty development programs for developing countries.